EVALUATION OF TRANSPORT INFRASTRUCTURE IN REGIONS OF THE CZECH REPUBLIC (Perner's Contacts, 2011)
This paper is focused on evaluation of transport infrastructure in regions of the Czech Republic. The main goal is to perform statistical analysis of selected indicators in years 2004–2009. The results showed that the transport infrastructure is not equally distributed. Higher density of transport network is typical for smaller regions in the northern part of the Czech Republic while large and/or peripheral regions are lacking behind. During the selected period, no significant changes in analyzed regions were observed.
Keywords: region; regional competitiveness; transportation; transport infrastructure